Genetic Evaluation of Growth Traits in Large White Yorkshire Crossbred Pigs using Random Regression Models - Devi, Kopparthi Sakunthala; Sindhu, Gadiparthi; Reddy, Punuru Panduranga; Chakravarthi, Matha Kalyan (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The objective of the present study was to determine the heritability estimates and breeding values of body weights in Large White Yorkshire crossbred pigs using random regression models. Data obtained from 51,302 records of 4653 animals, progeny of 155 sires and 291 dams was subjected to random regression analysis using Legendre polynomials of order of fit 3, 4 and 5. Based on AIC values, random regression model with homogenous error variance and order of fit 3 for direct genetic, maternal genetic, maternal permanent environmental, and individual permanent environmental effects was found to be the best model. The first Eigen value accounted for more than 95% of the total genetic variation. The direct genetic heritability estimates tended to increase over time ranging from 0.02±0.00 at 1st week to 0.88±0.08 at 24 weeks of age. The average estimated breeding value for birth weight was 1.15 kg which increased to 39.38 kg at 24 weeks of age.